2004
DOI: 10.1080/15287390490493466
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Performance Studies of Water Lettuce, Duckweed, and Algal-Based Stabilization Ponds Using Low-Strength Sewage

Abstract: A bench-scale continuous-flow wastewater treatment system comprising three parallel lines using duckweed (Spirodela polyrhiza), water lettuce (Pistia stratiotes), and algae (natural colonization) as treatment agents was set up to determine environmental conditions, fecal coliform profiles and general treatment performance. Each line consisted of four ponds connected in series fed by diluted sewage. Influent and effluent parameters measured included environmental conditions, turbidity, biochemical oxygen demand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 22 publications
2
28
0
Order By: Relevance
“…When anions are taken up more rapidly than cations, the roots release bicarbonate and hydroxyl ions into solution and the pH of the medium rises. Another explanation for the fluctuation in pH is the consumption of carbon dioxide (CO 2 ) during algal photosynthesis and the production of CO 2 during organic matter decomposition [34,55,56] . According to Lawson [2] and Meade [36] , the pH of waters used for the culture of fish and shellfish should range from 6.5 to 8.0.…”
Section: Phosphate-phosphorusmentioning
confidence: 99%
“…When anions are taken up more rapidly than cations, the roots release bicarbonate and hydroxyl ions into solution and the pH of the medium rises. Another explanation for the fluctuation in pH is the consumption of carbon dioxide (CO 2 ) during algal photosynthesis and the production of CO 2 during organic matter decomposition [34,55,56] . According to Lawson [2] and Meade [36] , the pH of waters used for the culture of fish and shellfish should range from 6.5 to 8.0.…”
Section: Phosphate-phosphorusmentioning
confidence: 99%
“…The fecal bacteria could be removed from water attaching to floating aquatic macrophytes [16]. Awuah et al [17] studied duckweed and algal pond system and established that macrophytes pond systems performed better in the removal of coliforms. The numbers of Enterobacteriaceae colony forming units per milliliter of water average varied from 5.13x10 3 to 6.27x10 3 respectively in the control and experimental system ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Given the large amount of literature available on constructed wetlands, we like to refer to (a) Hoffmann et al (2011) for the recent technology review of constructed wetlands; (b) Rose (1999) for wetland applications in urban farming; and (c) Ludwig (2009) for small-scale and household-based greywater treatment, including constructed wetlands. In West Africa, the use of pond systems with duckweed or water lettuce has been reported, for example, from Senegal, Burkina Faso, Ghana and Niger (Rose 1999;Awuah et al 2004;Koné et al 2002;Quayle 2012). In Kumasi, constructed wetlands as well as macrophyte-based treatment systems have been studied, for example, by Awuah et al (2004) and Niyonzima (2007).…”
Section: Trench Filter Beds and Constructed Wetlandsmentioning
confidence: 99%
“…In West Africa, the use of pond systems with duckweed or water lettuce has been reported, for example, from Senegal, Burkina Faso, Ghana and Niger (Rose 1999;Awuah et al 2004;Koné et al 2002;Quayle 2012). In Kumasi, constructed wetlands as well as macrophyte-based treatment systems have been studied, for example, by Awuah et al (2004) and Niyonzima (2007). Awuah et al (2004) reported achieving a fecal coliform removal of 6, 4 and 3 log units for algae ponds, duckweed ponds and water lettuce, respectively.…”
Section: Trench Filter Beds and Constructed Wetlandsmentioning
confidence: 99%
See 1 more Smart Citation